Pengaruh Digital Marketing sebagai Sarana Penjualan terhadap Tingkat Kinerja Pemasaran: Pedagang Kaki Lima di Sepanjang Pintu 1-4 Universitas Sumatera Utara - Siahaan, Nazwa Adam’s; Rossevelt, Franklin Asido; Aisyah, Dara; Panjaitan, Irna Dela Yunitha; Panjaitan, Engzellyski; Hutauruk, Onida; Jannah, Mifthahul (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the influence of digital marketing as a sales tool on the marketing performance of street vendors (PKL) along Gates 1–4 of the University of North Sumatra. The background of the study is based on the increasing use of social media, especially Instagram, as a promotional and marketing communication tool in the informal sector. The study used a quantitative approach with a non-probability sampling technique, and data collection through a five-point Likert scale questionnaire. The results of the validity and reliability tests showed that the research instrument met the eligibility criteria, although one item in the digital marketing utilization variable was declared invalid. Correlation analysis showed a strong positive relationship between variables, while the results of multiple linear regression proved that digital marketing (X1) and its utilization through Instagram (X2) had a significant effect on marketing performance (Y), both partially and simultaneously. The coefficient of determination (R² = 0.819) indicated that 81.9% of the variation in marketing performance was explained by the two independent variables. These findings confirm that the existence of digital accounts and active content management through Instagram play an important role in increasing business visibility, attracting customers, and encouraging increased sales of street vendors in the area. Thus, digital marketing is a relevant and effective strategy in strengthening the competitiveness of small businesses in the digital era.